Human tau increases amyloid β plaque size but not amyloid β‐mediated synapse loss in a novel mouse model of Alzheimer's disease. (12th November 2016) - Jackson, Rosemary J.; Rudinskiy, Nikita; Herrmann, Abigail G.; Croft, Shaun; Kim, JeeSoo Monica; Petrova, Veselina; Ramos‐Rodriguez, Juan Jose; Pitstick, Rose; Wegmann, Susanne; Garcia‐Alloza, Monica; Carlson, George A.; Hyman, Bradley T.; et al.
Abstract: Alzheimer's disease is characterized by the presence of aggregates of amyloid beta (Aβ) in senile plaques and tau in neurofibrillary tangles, as well as marked neuron and synapse loss. Of these pathological changes, synapse loss correlates most strongly with cognitive decline. Synapse loss occurs prominently around plaques due to accumulations of oligomeric Aβ. Recent evidence suggests that tau may also play a role in synapse loss but the interactions of Aβ and tau in synapse loss remain to be determined. In this study, we generated a novel transgenic mouse line, the APP/PS1/rTg21221 line, by crossing APP/PS1 mice, which develop Aβ‐plaques and synapse loss, with rTg21221 mice, which overexpress wild‐type human tau. When compared to the APP/PS1 mice without human tau, the cross‐sectional area of ThioS+ dense core plaques was increased by ~50%. Along with increased plaque size, we observed an increase in plaque‐associated dystrophic neurites containing misfolded tau, but there was no exacerbation of neurite curvature or local neuron loss around plaques. Array tomography analysis similarly revealed no worsening of synapse loss around plaques, and no change in the accumulation of Aβ at synapses. Together, these results indicate that adding human wild‐type tau exacerbates plaque pathology and neurite deformation but does not exacerbate plaque‐associated synapse loss. Abstract : Interactions of amyloid and tau pathologies in a transgenic mouse model of Alzheimer's disease: overexpressing human wild‐type tau in the APP/PS1 transgenic mouse model caused increased plaque size and more dystrophic neurite accumulation around plaques but did not worsen other pathological phenotypes including synapse loss and neuron loss around plaques.